Correlation between the level of self-confidence and anxiety with the performance of karate athletes kata class - Aryani, Mela; Maulana, Rizki; Afriyuandi, Asep Ramdan (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Purpose: The aim of this research was to see correlation between levels of self-confidence and anxiety and the performance of karate athletes. Method: This research was carried out at the Dojo of SMPN 1 Campaka Cianjur with a sample of 40 people, the technique of taking samples with a total sample was that the entire population was used as a sample. The research method used is quantitative descriptive with correlational analysis. The instrument used is the CSAI-2 questionnaire to measure cognitive anxiety, somatic anxiety and self-confidence. Data is collected online using Google Form. This research was calculated using IBM SPSS Statistics 26 which measures the Normality test and the Pearson product moment hypothesis test. Result: The results of this study state that there is a correlation between the level of self-confidence and the performance of karate athletes in the kata class with a significance value of 0.001, there is a correlation between the level of anxiety and the performance of karate athletes in the kata class with a significance value of 0.000, there is a correlation between the level of self-confidence and anxiety and performance kata class karate athlete with a significance value of 0.000.